Type-specific dendritic integration in mouse retinal ganglion cells - Yanli Ran (Nature Portfolio, 2020)
Neurons compute by integrating synaptic inputs across their dendritic arbor. Here, the authors show that distinct cell-types of mouse retinal ganglion cells that receive similar excitatory inputs have different biophysical mechanisms of input integration to generate their unique response tuning.